Synteza na lekcjach języka polskiego = Synthesis of Polish Language Lessons - Cofalik, Jan (1911-2001) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
After preliminary considerations about the essence of historical and literary synthesis the author describes, analyses and estimates traditional ways of bringing to pass syntheses of teaching. The pupils did not manifest any major independence nor activity and acquired onlya ready-for-use synthesis from the textbook or the teacher's lecture, who played a leading part in ending in generalizations. The author also cautions against ostensible, vapid, hasty or unreliable syntheses.
Keywords: dydaktyka literatury; język polski - nauczanie